1980
DOI: 10.1507/endocrj1954.27.285
|View full text |Cite
|
Sign up to set email alerts
|

Negative feedback effects of chlormadinone acetate and ethynylestradiol on gonadotropin secretion in patients with prostatic cancer and male rats.

Abstract: Serum LH and FSH levels were determined before and after LH-RH injection (100 micrograms, i.m.) in patients with prostatic cancer who were chronically treated with either chlormadinone acetate (CMA, 100 mg/day) or ethynylestradiol (EE, 1 mg/day). In patients treated with EE, the levels of serum LH and FSH before and after injection of LH-RH were significantly lower than those in controls. On the other hand in patients treated with CMA, the basal levels of serum gonadotropins did not differ from those in contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In the male rat, estrogens negatively feed back to central regulatory centres thereby reducing luteinizing hormone and testosterone release (Noguchi et al 1980;Anderson et al 1991). Accordingly, the atrophy of Leydig cells that occurred with high incidence at 0.2 mg ethinylestradiol/kg in both studies is readily explained as a consequence of reduced luteinizing hormone secretion (Wing et al 1985).…”
Section: Discussionmentioning
confidence: 83%
“…In the male rat, estrogens negatively feed back to central regulatory centres thereby reducing luteinizing hormone and testosterone release (Noguchi et al 1980;Anderson et al 1991). Accordingly, the atrophy of Leydig cells that occurred with high incidence at 0.2 mg ethinylestradiol/kg in both studies is readily explained as a consequence of reduced luteinizing hormone secretion (Wing et al 1985).…”
Section: Discussionmentioning
confidence: 83%
“…This suggests that our results were relatively higher than those of their report. The relatively low levels of LH and FSH in their report may be related to the negative feedback effect of the estrogen contained in COC on gonadotropin‐releasing hormone secretion 25,26 …”
Section: Discussionmentioning
confidence: 93%
“…The relatively low levels of LH and FSH in their report may be related to the negative feedback effect of the estrogen contained in COC on gonadotropin-releasing hormone secretion. 25,26 A phase I/II study in Europe reported that the 24/4 dosing of DRSP did not reinstate ovulation until 9 days after the end of the dosing. 27 DRSP has also been shown to suppress ovulation even with intentional 24 h intake delay.…”
Section: Discussionmentioning
confidence: 99%